Short-term changes in thermal conditions and active layer thickness in the tundra of the Kaffiøyra region, NW Spitsbergen - Sobota, Ireneusz; Dziembowski, Michał; Grajewski, Tomasz; Weckwerth, Piotr; Nowak, Marcin (Bulletin of Geography. Physical Geography Series, 2016)
This article describes and discusses the results of observations concerning short-term changes in the thermal conditions and the thickness of the active layer in a test field located in the tundra of the Kaffiøyra (NW Spitsbergen) during the summer season of 2015. One of the objectives was to find a correlation between the dynamic of the changes and the local topography. In recent years, thawing of the active layer in the Kaffiøyra region has been considerably varied in individual summer seasons. The test field area was 100 square meters, comprised 36 measurement points and was situated at approximately 3 m a.s.l. in the tundra. The measurements of the thickness and temperature of the active layer were carried out in July, August and early September of 2015. The greatest thickness of the active layer in the tundra was found near the moraine, in the area with the sharpest slope (156 cm to 212 cm). Ground temperatures were observed to follow the prevailing weather conditions with a delay, which amounted to about 24 h at a depth of 25 cm, and as much as 48 h at a depth of 75 cm. A greater thickness of the active layer was found in the western part of the test field, in the vicinity of a tidal channel, and in the eastern part of the field, bordering on the foot of the Aavatsmarkbreen’s moraine. A considerable sloping of the land, combined with increased surface runoff and infiltration at the time of precipitation, makes the water penetrating into the active layer increase its temperature. This demonstrates that the local land forms (tidal channels and terminal moraines) have a substantial influence on the extent and rate of changes which occur in the active layer.